Lithium doped biphasic calcium phosphate: Structural analysis and osteo/odontogenic potential in vitro - Yoo, Kyung-Hyeon; Kim, Yeon; Kim, Yong-Il; Bae, Moon-Kyoung; Yoon, Seog-Young (Frontiers in Bioengineering and Biotechnology, 2022)
Biphasic calcium phosphate (BCP) is generally considered a good synthetic bone graft material with osteoinductive potential. Lithium ions are trace elements that play a role in the bone-remodeling process. This study aimed to investigate the effects of lithium ions on the phase, crystal structure, and biological responses of lithium doped BCPs and to identify improvements in their osteogenic properties. Lithium-doped BCP powders with different doping levels (0, 5, 10, and 20 at%) were synthesized via the co-precipitation method. We found that the four types of lithium-doped BCP powders showed different phase compositions of hydroxyapatite and β-tricalcium phosphate. In addition, lithium ions favored entering the β-tricalcium phosphate structure at the Ca (4) sites and calcium vacancy sites [VCa(4)] up to 10 at%. This substitution improves the crystal stabilization by filling the vacancies with Ca2+ and Li+ in all Ca sites. However, when the concentration of Li ions was higher than 10 at%, lithium-induced crystal instability resulted in the burst release of lithium ions, and the osteogenic behavior of human dental pulp stem cells did not improve further. Although lithium ions regulate osteogenic properties, it is important to determine the optimal amount of lithium in BCPs. In this study, the most effective lithium doping level in BCP was approximately 10 at% to improve its biological properties and facilitate medical applications.